Pengaruh Akuntabilitas, Partisipasi, Dan Prinsip Efisiensi Pengelolaan Anggaran Pendapatan Dan Belanja Sekolah Terhadap Kinerja Pegawai Pada SMP Negeri Simpang Kiri Kota Subulussalam - Lestari, Yuli; Nurlina, Nurlina; Azhar, Iqlima (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
This study aims to determine the effect of accountability,participation, and the principle of efficiency of school budget management on employee performance at Simpang Kiri Junior High School Subulussalam. This study uses quantitative data by distributing questionnaires to respondents to be assessed or scored on each respondent's answer. Sources of data used in this study are primary data obtained and collected from data collection questionnaires given to respondents in SMP Negeri Simpang Kiri Subulussalam. The sample used in this study is saturated sampling. the number of samples in this study as many as 67 respondents with all employees as respondents, which include principals, treasurers, TU, and teachers in SMP Simpang Kiri Subulussalam. Meode used in this study is a quantitative method with IMB SPSS Analysis tool version 25. The results of the research accountability management of school budget has a positive and significant influence on employee performance at Simpang Kiri Junior High School Subulussalam, participation management of school budget has a positive and significant influence on employee performance at Simpang Kiri Junior High School Subulussalam, the principle of efficiency management of school budget has a positive and significant influence on employee performance, participation and the principle of efficiency in managing school budgets together have a positive and significant influence on employee performance at Simpang Kiri Junior High School in Subulussalam City.